Dating the Timeline of House Price Bubbles in Australian Capital Cities1. Issue 299 (29th June 2016) - Shi, Shuping; Valadkhani, Abbas; Smyth, Russell; Vahid, Farshid
Abstract : House prices in some Australian capital cities have recently been on the rise to the extent that some describe this as an emerging bubble, but this claim remains formally untested to date. We apply a recently developed time series procedure to detect, and time‐stamp, bubbles in house price to rent ratios in Australian capital cities. The results show a sustained, yet varying, degree of speculative behaviour in all capital cities in the 2000s before the 2008 global financial crisis (GFC) engulfing different housing markets. The onset of these bubbles was soon after the federal government introduced a major change to the capital gains tax law, and all of these bubbles collapsed with or before the GFC. As of January 2016 only Sydney exhibits significant evidence of an exuberant rise in house prices compared to rents. We believe that the method we apply has the potential to be a general early warning indicator to detect housing bubbles in other countries/markets. We provide the programming files to enable researchers to implement this test in other countries.